Smart Futures, Challenges of Urbanisation, and Social Sustainability (Springer International Publishing, 2018)
This book tackles the challenges posed by accelerating urbanization, and demystifies Social Sustainability, the least understood of all the different areas of sustainable development. The volume's twin focus on these profoundly intertwined topics creates a nuanced and vitally important resource. Large migrations from rural areas to cities without appropriate planning and infrastructure improvements, including housing, education and health care optimization, have created significant challenges across the globe. The authors suggest technology-rich strategies to meet these challenges by careful application of data on population growth and movement to the planning, design, and construction of operational infrastructures that can sustainably support our increasingly rapid population growth.